Descriptors validation for the morphological characterization of five cas accesions [Psidium friedrichsthalianum (O. Berg) Niedenzu] in Costa Rica - Monge-Solís, Jonathan (2023)
Introduction. According to Biodiversity International, a descriptor is defined as an attribute, or a measurable character that is observed in an accession of a genetic bank. The importance of the standardization of descriptors is based on generating information under a universal language. The characterization of crops is essential to assess their diversity, classification, conservation and exploitation, however the list of plants that have not been described is vast. The cas (Psidium friedrichsthalianum) is native to Costa Rica, whose fruit is very common, and its production and uses have increased in recent years, even though, it is almost an orphan studied crop. Objective. Validate a descriptors list and use it in the characterization of cas in the country, as opportunities for its genetic improvement may arise. Materials and methods. Descriptors and morphological characterization of different species of the Myrtaceae family were adapted and 5 accessions of Costa Rican creole located in 5 producing farms in the provinces of Cartago, San José, Heredia and Limón were evaluated in the field. Results. The field results, together with additional observations, were compared and possible discriminant descriptors within the Costa Rican creole cas were identified. Conclusions. it was developed a varietal descriptor to the morphologic characterization of Costa Rican creole cas and it was applied in different genetic accessions in the country. It got with the morlogic characterization that the variables calyx cavity diameter, petals number, relation long / fruit diameter, pistil long, relation long / leave width, fruit diameter and fruit long are possible discriminant descriptor to the Costa Rican creole cas.